2019
DOI: 10.1111/nmo.13541
|View full text |Cite
|
Sign up to set email alerts
|

More movement with evaluating colonic transit in humans

Abstract: Background Colonic functions (ie, absorption of fluids and electrolytes, digestion of selected nutrients, harbor for microbes, and elimination of excreta) necessitate complex patterns of storage and transit. Indeed, colonic transit accounts for a major part of the mouth‐to‐anus transit time. Colonic transit assessments are useful for understanding the pathophysiology of disease, the pharmacodynamic effects of new medications and to diagnose slow transit constipation. Currently, radiopaque markers, scintigraphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…For instance, Chan and colleagues [13] demonstrated that the mean total CTT in healthy Chinese adults was 24.5 h, which was very similar to the 23.08 h we observed in the HC group. Though a universal standard for CTT has not been established, 30 h is a commonly used benchmark for the standard colon transit time [11, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Chan and colleagues [13] demonstrated that the mean total CTT in healthy Chinese adults was 24.5 h, which was very similar to the 23.08 h we observed in the HC group. Though a universal standard for CTT has not been established, 30 h is a commonly used benchmark for the standard colon transit time [11, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…A single capsule containing 24 radio-opaque markers (Sitzmarks, Konsyl Pharmaceutical, TX, USA) was taken once per day for three consecutive days at 8 am. The protocol was similar to that described by Bharucha and some authors and colleagues [11]. Simple abdominal radiographs were taken at 8 am on day four of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of 3 times per minute accounts for more than 80% of the total rhythmic frequency. This rhythm pattern commonly occurs in the junction area between the sigmoid and rectum, where there is no functional sphincter according to some studies[22]. The absence of a functional sphincter can lead to dysfunction in the defecation process, which can explain the pathological mechanism of some functional constipation disorders[23,24].…”
Section: Segmental Movement Of the Colonmentioning
confidence: 99%
“…This coordinated spatiotemporal pattern has been suggested to play an important role in the shifting of colonic content in the rectal direction to prepare for defecation, as most individual HAPWs do not span the entire colon (9). The innervation of the colon also shows regional differences (9,58), and functional differences related to transit and storage are well documented (5,7,41). There have also been indications in the pediatric literature that HAPWs are not normal unless they span the entire colon (47), which makes it important to study regional HAPWs.…”
Section: Introductionmentioning
confidence: 99%